Musculoskeletal injury prevention plan(Original) (Revista científica Olimpia, 2020)
The investigation was developed utilizing soccer players of the social team of Granma province, due to the need to elaborate a plan of prevention motivated by the increment of the muscle-skeletal injuries that affect the sports performance and these athletes' health. We used theoretic, empiric and statistical methods to give fulfillment to the investigating tasks; Ross's and Kerr's method was utilized for the calculation of the fractioning of the corporal mass and we compared with referential values of Cuban sportsmen elites of masculine sex. As a result, it was found many factors, causes and mechanisms of the production of the injuries and that the most frequent are the esguinces of ankle for mechanism of over-use; and the elaboration of the prevention plan as from the analysis of the causal factors, following four steps, with a flexible character, integrative and with focus of system.
Keywords: muscle-skeletal injuries; corporal composition; health; sports performance; prevention.